Work in progress - fine-tuning an engineering study abroad program - Lineberry, G. T.; Lynch, Andrew; Keathley, Donnie; Wong, Janice; Bettez, David (IEEE, 2007)
The University of Kentucky (UK) College of Engineering (CoE) has had a long-standing credit-transfer relationship with INTI International University College (ENTI). In Spring 2006, two UK sophomores enrolled in ICM to begin what we hoped would be a vibrant and self- sustaining program. This paper will provide: an overview of the two institutions' motivation for starting this innovative study abroad program; a summary of the operational program details, including the participant support structure and efforts to ensure maximum course credit transferability; experiences of the first two participants, as recorded in a pre-departure guide; results of the recruitment and subsequent enrollment of the second study abroad cohort; and UK's formal program evaluation. Administrative details will be offered as counsel to other U.S. engineering colleges interested in study abroad relationships with similar American university programs. A more thorough overview of program benefits and current status is deferred until the paper presentation.